In vitro Comparison of Apical Debris Extrusion Using Rotary and Reciprocating Systems in Severely Curved Root Canals - Delvarani, Abbas; Mohammadzadeh Akhlaghi, Nahid; Aminirad, Raana; Vahdati, Seyed Aliakbar; Tour Savadkouhi, Sohrab (Iranian Endodontic Journal, 2017)
Introduction: The aim of this in vitro study was to compare the amount of apically extruded debris after root canal preparation using rotary and reciprocating systems in severely curved root canals. Methods and Materials: Thirty six extracted human mandibular first molars with 25-35° curvature in their mesiobuccal (MB) canal (according to Schneider’s method) were cleaned and shaped with ProTaper and WaveOne systems. The extruded debris was collected and their net weight was calculated. To compare the efficiency of the two systems, the operation time was also measured. The data were analyzed with t-test. Results: The amount of extruded debris in WaveOne group was significantly greater in comparison with ProTaper group (26%). The operating time for ProTaper was however, significantly longer than WaveOne. Conclusion: Both root preparation systems caused some degree of debris extrusion through the apical foramen. However, this amount was greater in WaveOne instruments. Keywords: Apical Extrusion; Curved Canals; Reciprocating File; Root Canal Preparation; Rotary Instrumentation